2019
DOI: 10.3390/su11020527
|View full text |Cite
|
Sign up to set email alerts
|

The Role of a Manager’s Intangible Capabilities in Resource Acquisition and Sustainable Competitive Performance

Abstract: The answer to the challenging question, “Should one either invest in tangible resources or intangible resources/capabilities?” is still fragmented. In prior studies, more emphasis is given to tangible resources, while intangible resources have comparatively received minor attention, despite their significant role in the success of small and medium enterprises (SMEs). Particularly the role of the intangible skills; intellectual capital, financial literacy (FL), and business experience (BE) in resource acquisiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
3
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 80 publications
5
135
3
6
Order By: Relevance
“…All these systematic approaches have put forward compelling insights for the scope of the current endeavor, nevertheless they only set the premises for a more targeted outlook of the key variables. Given the fact that our search strategy did not return breakthrough approaches on the topic and in light of the findings of previous studies [30][31][32][33][34][35], we acknowledged the existence of a research gap and the imperative to provide an output for readers and researchers (i.e., a research agenda and/or a conceptual framework on the topic) liable to bring to the fore future research avenues.…”
Section: Summary Of the Main Findings And Future Research Avenuesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these systematic approaches have put forward compelling insights for the scope of the current endeavor, nevertheless they only set the premises for a more targeted outlook of the key variables. Given the fact that our search strategy did not return breakthrough approaches on the topic and in light of the findings of previous studies [30][31][32][33][34][35], we acknowledged the existence of a research gap and the imperative to provide an output for readers and researchers (i.e., a research agenda and/or a conceptual framework on the topic) liable to bring to the fore future research avenues.…”
Section: Summary Of the Main Findings And Future Research Avenuesmentioning
confidence: 99%
“…This situation is indicative of the fact that these studies have not discussed the relationships among the constructs/key variables in a comprehensive framework, but rather in tangential approaches, thus calling for more articulate and specific investigations. A new path towards further exploration of the underlying conceptual relationships between constructs and of the structural relationships between factors within more complex methodological designs is opened, all the more so as, nowadays, SMEs internationalization process cannot be framed anymore in the absence of intangible assets and sustainability views [14][15][16][17][18][19][30][31][32][33][34][35]129]. Moreover, taking into consideration the distribution criterion of articles with regard to the year of publication and the source journals most contributions have been published in (as depicted in Table 3), a growing interest has been displayed in academia and research for this topic or for related ones since 2011, as objectivized in top-ranked scientific outlets.…”
Section: Summary Of the Main Findings And Future Research Avenuesmentioning
confidence: 99%
“…Waldman et al [130] found a positive correlation between the intellectual stimulation dimension of CEO leadership and the propensity of a firm to be socially responsible. Ying et al [49] highlighted that the support to IC for a superior competitive advantage was largely driven by top management skills and engagement in fostering IC culture inside organizations. Altuner et al [29] proposed a triangulation among CG, IC, and CSR with the aim to demonstrate the positive linkages among these concepts and firm facets.…”
Section: The Link Between Cg As a Csr Pillar And Icmentioning
confidence: 99%
“…The findings of the meta-analyses range from small [44] to medium [45] to significantly positive links between CSR and financial performance [46]. On the other hand, we refer to the less-investigated theme of the impact of CSR on IC from a management perspective [15,27,28,[47][48][49]. To integrate these two lines of investigation, the present study assumes the concept of CSR as a "cospecialized asset" [37] (p. 1491) with the capacity to increase the value of other assets, which, in turn, contribute to the firm performance.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the interlinks between intellectual capital and sustainable regional competitiveness are strong and inseparable [30]. Also, the results of Ying's et al research indicate that intellectual capital helps managers in acquiring valuable resources, which in turn enhance sustainable competitive performance [31]. HC is defined as a measure of experience, enterprise databases, technologies and devices, knowledge and skills, and customer relationships.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%